2020
DOI: 10.1177/2158244019901253
|View full text |Cite
|
Sign up to set email alerts
|

Psychometry of the Multidimensional Perceived Autonomy Support Scale in Physical Education With Spanish Secondary School Students

Abstract: This research aimed to adapt and psychometrically examine the Multidimensional Perceived Autonomy Support Scale in Physical Education in the Spanish context. The participants were 560 (264 men and 296 women; Mage = 14.49, SDage = 1.05) physical education secondary school students. The results underpinned a 15-item three-factor correlated model, which was invariant across gender and age. The reliability analysis reflected an acceptable level of internal consistency and temporal stability for each factor. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
(60 reference statements)
2
11
0
1
Order By: Relevance
“…The comparison of the fits of the tested models indicates that the constructs of cognitive, organizational and procedural autonomy support represent factors that are conceptually and empirically distinguishable but highly relate to each other. This interpretation was also supported in studies validating the MD-PASS-PE in samples of secondary school students in Estonia and Spain [ 33 , 42 ].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The comparison of the fits of the tested models indicates that the constructs of cognitive, organizational and procedural autonomy support represent factors that are conceptually and empirically distinguishable but highly relate to each other. This interpretation was also supported in studies validating the MD-PASS-PE in samples of secondary school students in Estonia and Spain [ 33 , 42 ].…”
Section: Discussionsupporting
confidence: 58%
“…Former confirmatory factor analyses supported both a three-factor solution and a second-order model, which underlined the assumption of three conceptually distinct but highly related factors [ 33 ]. Further studies supported the reliability and factorial validity of the scale [ 42 , 43 , 44 , 45 ].…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…These authors considered that the students' perception of support teacher autonomy during PE classes was divided into three different dimensions: support for organizational autonomy, support for cognitive autonomy and support for procedural autonomy. This structure was later confirmed by Burgueño et al [22], but as the original scale towards the context of PE. The results showed that the new instrument, MD-PASS-PA, has adequate psychometric properties, being a reliable and valid instrument to measure autonomy support in a multi-dimensional way.…”
Section: Discussionsupporting
confidence: 55%
“…The results showed that each of the three factors supporting autonomy was positively associated with the satisfaction of psychological needs. This scale has also been validated towards the Spanish context of PE by Burgueño et al [22]. The authors performed both exploratory and confirmatory factorial analyses with independent samples, showing adequate psychometric properties and a three-factor structure for the questionnaire.…”
Section: Introductionmentioning
confidence: 99%